Pelatihan Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Problem Based Learning Berbasis HOTS pada Guru SD Negeri Inpres Koya Tengah Distrik Muara Tami - Hidayah Hidayah; Aplonia C. Yonggom; Mamberuman Marthen Inggamer; Chelsi Yuliana S.; Tiffany Shahnaz Rusli (J-Abdimas Cenderawasih, 2023)
In preparing the Learning Implementation Plan, it is necessary to pay attention to indicators such as the application of learning models based on material needs so that the implementation of learning is more active, innovative and focused. One of the innovative and creative learning models to be applied in the learning process is Problem Basic Learning (PBL). The Problem Basic Learning (PBL) learning model invites students to solve problems independently. This service aims to equip and provide experience to teachers at SD Negeri Inpres Koya Tengah, Muara Tami Jayapura District in preparing learning implementation plans by implementing the Problem Based Learning (PBL) model with Hots-based learning implementation and improving the quality of learning in the school. This service activity was carried out in the form of training for teachers at the school which was attended by 12 teachers. The training method used is mentoring in the form of lectures, questions and answers and discussions. This activity includes: 1) preparation in planning the implementation of training conceptually, operationally and job descriptions, 2) implementation of the presentation of RPP material on the Problem Based Learning model and how to prepare a Hots-based Learning Implementation Plan. 3) Evaluation and discussion include the practice of making lesson plans by participants, collecting practical assignments, assessing the results of the training participants' work, and reflecting on the training material. The output of this service activity is achieving the objectives of this training and creating articles that will be published in community service journals.